Toxicity effect of Annona reticulata seed extract against bean aphid, Aphis craccivora Koch - Bhuyain, Mohammad Mosharof Hossain; Uddin, Md Nizam; Bachchu, Md Adnan Al; Ahmed, Toufiq (Fundamental and Applied Agriculture, 2016)
Bean aphid is one of the major destructive pests to country bean in Bangladesh. Therefore, an investigation was carried out to evaluate the efficacy of Annona reticulata L. seed extract in six different solvents viz., ethylalcohol, ethylacetate, acetone, chloroform, dichloromethane and n-hexane for their toxicity and repellent effects against bean aphid, Aphis craccivora Koch applied. Three different doses (0.25, 0.50 and 1.0 g mL-1) with each solvent extract were used in the laboratory. The results revealed that A. reticulata seed extracts had direct toxic and repellent effects on bean aphid. The highest mortality was observed in the ethylalcohol extracts at 24 and 48 hours after treatments. Considering LD50 values, it was observed that the extract in different solvents show toxicity in order of ethyl alcohol > n-hexane > chloroform > dichloromethane > ethyl acetate > acetone. Mortality percentages of all solvent extracts were directly proportional to the level of concentration and hours after treatment. The results also showed the repellency effect against A. craccivora. Among different doses, 1.0 mg mL-1 had the highest insect mortality and repellency. The highest repellency was observed in ethyl alcohol extract (72.89%) and the lowest repellency was observed in acetone extracts (60.04%). All solvent extracts except acetone showed in the same repellency class i.e. class IV. Based on the mean repellency rate, it was found that all concentrations possess the same repellency class i.e. class IV.